Regional Economic Outlook, May 2009, Western Hemisphere : Stronger Fundamentals Pay Off. (Regional Economic Outlook, 2009)
The global crisis that began in advanced economies has sent severe shocks around the world, posing a test to the economies of Latin America and the Caribbean. The good news is that during this decade the region has made itself more resilient to external shocks, by strengthening policy frameworks and reducing vulnerabilities in its public finances and financial systems. These preparations, the report shows, mean that countries are now more able to respond to the external crisis, many for the first time, with active policies to boost output and employment and protect the most vulnerable groups. This will help contain the damage from the global crisis and speed up the region's recovery.